Construction problems of criminological indicators and comparative situation of femicide in Peru - Mujica, Jaris (2012)
Like other countries in the region, femicide—the gender-based murdering of women—has been incorporated into Peruvian law as a criminal offense. This inclusion is the result of the government and civil society organizations interest in producing policies aimed at reducing gender-based violence, and it has emerged as a result of a debate regarding «the increase in femicide» and the systematic appearance of media stories and official reports warning of an exponential growth. This article focuses upon the problem of femicide in Peru through a comparative approach. The aim is to account for the incidence of femicide in sociometric terms and demonstrate that this is not a phenomenon of exponential growth in epidemiological terms. This is achieved through the recognition of two issues: on the one hand, the way indicators are produced for criminal record figures and the ways these are measured; and on the other hand, through recognition of the importance of the significance of this phenomenon within a more complex and broader structure of violence.